The Effect of Using Microsoft Teams on The Eighth Graders’ Reading Assignments Outcomes - Rachma, Aulia Annisya; Kurniasih, Esti (Tarbiatuna: Journal of Islamic Education Studies, 2024)
This study investigates the extent to which Microsoft Teams influences the reading assignment outcomes of eighth graders in Junior High School. The research objective was to assess the effect of utilizing Microsoft Teams as a digital method for delivering reading assignments. A quantitative approach employing a one-group pre-test post-test design was utilized. The researcher administered a series of tests including pre-test and post-test. The results indicate there has an effect of Microsoft Teams on the eighth graders’ reading assignment outcomes. Statistical analysis revealed substantial differences between pre-test and post-test scores, suggesting improved performance due to the digital intervention.